Availability, accessibility, and quality of adolescent Sexual and Reproductive Health (SRH) services in urban health facilities of Rwanda: a survey among social and healthcare providers - Pacifique Ndayishimiye; Rosine Uwase; Isabelle Kubwimana; Jean de la Croix Niyonzima; Roseline Dzekem Dine; Jean Baptiste Nyandwi; Justin Ntokamunda Kadima (BMC, 2020)
Abstract Background Adolescents are still getting pregnant and contracting Human Immunodeficiency Virus (HIV) and Sexually Transmitted Infections (STIs) in Rwanda as elsewhere. Quality and comprehensive SRH services and information for adolescents is valuable for adolescents' wellbeing. This study aimed at understanding SRH services providers' viewpoints on accessibility, availability, and quality of SRH services provided to adolescents in selected cities of Rwanda. Method The study was a descriptive cross-sectional survey conducted between May 2018 and May 2019 in six selected cities of Rwanda using a mixed-methods approach. A checklist was used to collect data from 159 conveniently selected SRH services providers. The survey tool was validated. SPSS version 20 was used to describe quantitative data and ATLAS TI version 5.2 was used to code and analyze the qualitative data thematically. Results Qualitatively, health care providers reported that the availability of adolescent SRHS are satisfactory with access to accurate SRH information, contraceptive methods, prevention and management of STIs and HIV services, and counselling. However, the accessibility of some services remains limited. According to respondents, some products such as female condoms are less in demand and often expire before they can be distributed. One nurse clarified that they render services at a low price if an adolescent has insurance medical coverture. Religious leaders and family members may hinder adolescents from health-seeking behavior by promoting abstinence and discouraging use of protective means. Quantitatively, we found that 94.3% of health facilities provide information to adolescents on SRH services that were available and 51.6% affirmed delivering services at a low cost. Only 57.2% of respondents mentioned that adolescents are involved in designing the feedback mechanisms at their facilities. Conclusion SRH services in Rwanda are available for the general population and are not specifically designed for adolescents. These SRH services seem to be fairly accessible to adolescents with insufficient quality as adolescents themselves do not get to be fully involved in service provision among other aspects of quality SRH as stated by the World Health Organization (WHO). Therefore, there is a need to improve the present quality of these services to meet adolescents' needs in an urban setting.